THE ELEMENTS OF THE TOURISTIC SPACE OF THE BRAZIL-BOLIVIA BORDER - FIGUEIREDO, Nilze Paula; COSTA, Edgar Aparecido; PAULA, Beatriz Lima (UFPR, 2011)
The geographical space aimed by this study was the Brazil-Bolivia border, involving the urban areas of the Brazilian city, Corumbá, and the Bolivian ones, Puerto Quijarro and Puerto Suárez.   The objective of this study was to analyze the touristic border spaces, speculating about their similarities and divergences regarding integrated planning. Secondary data, resulting from field work, was used in the methodology. The border generates a tangled web of relationships and streams. The presented spatial elements mix complex rationalities, sometimes approaching, sometimes denying and even disregarding the possibilities that can be translated by the border.